RANCANG BANGUN SISTEM INFORMASI TRANSAKSI PEMBAYARAN TAGIHAN AIR CSR AQUA BERBASIS ANDROID (STUDI KASUS DESA CIHERANG PONDOK) - Anis Humanisa; Dina Agusten; Fauziah Fauziah; Meta Meysawati (Jurnal Teknik dan Science, 2022)
CSR Aqua Desa Ciherang Pondok is an Aqua company dedicated to providing clean water for the residents of Ciherang Pondok Village. Manual systems (notebooks and applications in Microsoft Excel) are still used to collect meter recording and water payments, so there are often errors in the recording process and do not respond to the excel documents created. In addition, the payment process takes a lot of time so it is less efficient. One of the functions that can be utilized is to create an online water payment system. Based on the existing problems, an application for information system for paying water bills CSR Aqua Desa Ciherang Pondok Barbasis Android was created. The research method uses the SDLC (System Development Life Cycle) waterfall approach, namely planning, implementation and testing. Applications are created using the Dart programming language and the Flutter framework. The results of the application were tested on several smartphone devices. Based on the test results, the application works well at least with the android 9.0 (pie) operating system.